Global phenology maps reveal the drivers and effects of seasonal asynchrony - Drew E. Terasaki Hart; Thảo-Nguyên Bùi; Lauren Di Maggio; Ian J. Wang (Nature, 2025)
Abstract Terrestrial plant communities show great variation in their annual rhythms of growth, or seasonal phenology1,2. The geographical patterns resulting from this variation, known as land surface phenology (LSP)3, contain valuable information for the study of ecosystem function4,5, plant ecophysiology6–8, landscape ecology9,10 and evolutionary biogeography11–13. Yet globally consistent LSP mapping has been hampered by methods that struggle to represent the full range of seasonal phenologies occurring across terrestrial biomes14, especially the subtle and complex phenologies of many arid and tropical ecosystems1,15,16. Here, using a data-driven analysis of satellite imagery to map LSP worldwide, we provide insights into Earth’s phenological diversity, documenting both intercontinental convergence between similar climates and regional heterogeneity associated with topoclimate, ecohydrology and vegetation structure. We then map spatial phenological asynchrony and the modes of asynchronous seasonality that control it, identifying hotspots of asynchrony in tropical mountains and Mediterranean climate regions and reporting evidence for the hypothesis that climatically similar sites exhibit greater phenological asynchrony within the tropics. Finally, we find that our global LSP map predicts complex geographical discontinuities in flowering phenology, genetic divergence and even harvest seasonality across a range of taxa, establishing remote sensing as a crucial tool for understanding the ecological and evolutionary consequences of allochrony by allopatry.